The Evaluation of Teaching Factory in SMK Negeri 2 Adiwerna Using CIPPO Model - Rangga, Sagita; Qudus, Nur; Endroyo, Bambang (Journal of Vocational and Career Education, 2020)
Teaching factory implementation is expected to be link and match between school and industrial world to produce competent graduates who can meet the demand of industry. In its implementation, teaching factory requires teachers to understand its concepts, technicality, and implementation. Evaluation is necessary to be conducted to obtain an overview of the success and benefits of teaching factory. However, recent evaluations have only focused on the aspects of results and constraints, yet the whole evaluation is the one that is significant to carry out. Therefore, this research attempted to evaluate teaching factory using CIPPO (Context, Input, Process, Product, Outcome) model. It analyzed the implementation of Teaching Factory in Adiwerna 2 Public Vocational High School or SMK Negeri 2 Adiwerna, the success and benefit levels of teaching factory viewed from the aspects of context, input, process, product, and outcome in SMK Negeri 2 Adiwerna, and factors constraining the implementation of it. To do so, the researchers employed quantitative method through questionnaire, interview, and documentation as the data collection instruments. For the analysis, the research used percentage description system. The data analyzed were collected from research subjects including the principal, vice principal in in charge of facilities and infrastructure, vice principal in charge of curriculum, the head of Computer and Network Engineering (CNE), Internship Group, Special Job Market (SJM), teachers, and students in grade XI who studied productive subject of CNE and business / industrial world. The results showed that: (1) overall, the implementation of teaching factory in SMK Negeri 2 Adiwerna run fairly well. (2) the context aspect gained the mean percentage of 64% in the fairly good category, the input aspect gained the mean percentage of 71% in the fairly good category, the process aspect gained the mean percentage of 74% in the fairly good category, the product aspect gained the mean percentage of graduates was 62% in the fairly good category, the outcome aspect gained the mean percentage of 84% in the good category. All those aspects obtained the mean percentage of 71% in the fairly good category. (3) there found several factors constraining teaching factory implementation and things to improve in the aspects of context and input. The context aspect lacked of cooperation with business / industrial world in the procurement of facilities and training with the mean percentage of 40% in poor category so that the subjects taught were less synchronized with the real situation in business/ industrial world. Meanwhile, the product aspect or the graduates who were absorbed into business/ industrial world were less optimal that based on the tracing data, the graduates of CNE in 2019 who were absorbed into business/ industrial world was 40% in the poor category. This calculation was even less optimal since there left 31 students of 94 with the percentage of 32.98% who have not yet given report so that it contributed to significant calculation results.